1994
DOI: 10.1117/12.177350
|View full text |Cite
|
Sign up to set email alerts
|

<title>Visual acuity versus field of view and light level for night vision goggles (NVGs)</title>

Abstract: Visual acuity (resolution) and field of view are two significant parameters used to characterize night vision goggles (NVG5). Most users of NVGs surveyed within the US Air Force put these two parameters at the head of the list of characteristics that they would like to see improved. Unfortunately, it is well established that these two parameters are coupled together in an inverse relationship: an increase in field of view results in a reduction in visual acuity and vice versa. However, there are at least two w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…We note that an increase in FOV results in a reduction in resolution (Donohue-Perry, Task, & Dixon, 1994;Genco, 1985). Next, we measured several tasks involving depth perception, and varied FOV.…”
Section: Reduced Visual Acuitymentioning
confidence: 97%
“…We note that an increase in FOV results in a reduction in resolution (Donohue-Perry, Task, & Dixon, 1994;Genco, 1985). Next, we measured several tasks involving depth perception, and varied FOV.…”
Section: Reduced Visual Acuitymentioning
confidence: 97%
“…(Figure 3) (AN/AVS-6 and AN/AVS-9). One major design characteristic of these NVGs is that increased FOV could only be obtained at the expense of resolution [3], [4] since each ocular uses only a single image intensifier tube. The image intensifier tube has a fixed number of pixels (picture elements).…”
Section: Introductionmentioning
confidence: 99%
“…The competing concepts of fixed contrast criteria versus contrast threshold function criteria for resolution (NVG-aided visual acuity assessment) was addressed by Donohue-Perry et al 24 when investigating the field of view effects on NVGaided visual acuity. Their results indicated that the fixed modulation level criteria approach provided an excellent fit to their data.…”
Section: Nvg Mtf and Resolution Assessmentmentioning
confidence: 99%
“…The field of view of the NVGs also can affect the NVG-aided visual acuity obtained because larger fields of view are obtained by shorter focal length lenses (objective and eyepiece lenses), which spread the fixed number of pixels of the image intensifier tube over a larger angular subtense. In general, the larger the field of view the worse the visual acuity level 24 . In addition, the eyepiece diopter setting can interact with the observer's ability to accommodate to the image distance, which in turn can affect the NVG-aided visual acuity obtained 29,30 .…”
Section: Variables That Affect Nvg-aided Visual Acuity Measurementmentioning
confidence: 99%
See 1 more Smart Citation